Dampak strategi komunikasi visual terhadap performa bank muamalat - Hasanah, Siti Aisyatul (Maliki Interdisciplinary Journal, 2025)
Visual communication has become a crucial element in marketing and communication strategies, particularly for financial institutions like Bank Muamalat, which is based on Islamic principles. This study aims to analyze the impact of visual communication on the performance of Bank Muamalat, focusing on enhancing brand awareness, customer loyalty, and emotional connections with clients. Through the application of various visual elements such as infographics and promotional videos, Bank Muamalat is able to convey information about its products and services in a more engaging and easily understood manner. The findings indicate that effective visual communication not only increases brand recognition but also strengthens customers’ attachment to the Islamic values upheld by the bank. Despite challenges in innovation and adaptation to technological advancements, recommendations for optimizing digital content and personalizing customer experiences can help Bank Muamalat remain relevant in a competitive market. This study affirms that visual communication is an integral strategy for achieving better business objectives in the banking industry.